Characterization of telomere-subtelomere junctions in Silene latifolia - Sýkorová, E; Cartagena, J; Horáková, M; Fukui, K; Fajkus, J (Molecular genetics and genomics, 2003)
Telomere-associated regions represent boundaries between the relatively homogeneous telomeres and the subtelomeres, which show much greater heterogeneity in chromatin structure and DNA composition. Although a major fraction of subtelomeres is usually formed by a limited number of highly repeated DNA sequence families, their mutual arrangement, attachment to telomeres and the presence of interspersed unique or low-copy-number sequences make these terminal domains chromosome specific. In this study, we describe the structures of junctions between telomeres and a major subtelomeric repeat of the plant Silene latifolia, X43.1. Our results show that on individual chromosome arms, X43.1 is attached to the telomere either directly at sites corresponding to nucleosome boundaries previously mapped in this sequence, or via other spacer sequences, both previously characterized and newly described ones. Sites of telomere junctions are non-random in all the telomere-associated sequences analysed. These data obtained at the molecular level have been verified using in situ hybridization to metaphase chromosomes and extended DNA fibres.
Keywords: tandemové repetitivní sekvence; Silene; DNA, Plant; sekvence nukleotidů; Chromosomes, Plant; telomery; In Situ Hybridization, Fluorescence; Molecular Sequence Data; sekvenční homologie nukleových kyselin; X Chromosome; molekulární sekvence - údaje; Tandem Repeat Sequences; chromatin; Terminal Repeat Sequences; genetická variace; Chromatin; Genetic Variation; chromozom X; Telomere; nukleozomy; Base Sequence; hybridizace in situ fluorescenční; Sequence Homology, Nucleic Acid; Nucleosomes; koncové repetice; DNA rostlinná; chromozomy rostlin